1997
DOI: 10.1161/01.cir.96.2.550
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Defects

Abstract: Although most fetal cardiac anomalies are detectable early in gestation, some may evolve in utero at different stages of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(52 citation statements)
references
References 29 publications
0
48
0
4
Order By: Relevance
“…In our country, most fetal examinations are covered by major health insurance organizations. Fetal cardiac examination is standardized using the extended protocol for fetal echocardiography, as previously reported by us [6][7][8][9] . This routinely includes seven sonographic views: (1) transverse view of the upper abdomen; (2) four-chamber view; (3) longitudinal left outflow tract; (4) short-axis view for right outflow tract; (5) longitudinal view for aortic arch and ductus; (6) longitudinal view for systemic veins; and (7) upper axial mediastinal, three-vessel view combined with tracheal location for aortic arch abnormalities.…”
Section: Accepted 21-8-02 Ultrasound In Obstetrics and Gynecologymentioning
confidence: 99%
See 1 more Smart Citation
“…In our country, most fetal examinations are covered by major health insurance organizations. Fetal cardiac examination is standardized using the extended protocol for fetal echocardiography, as previously reported by us [6][7][8][9] . This routinely includes seven sonographic views: (1) transverse view of the upper abdomen; (2) four-chamber view; (3) longitudinal left outflow tract; (4) short-axis view for right outflow tract; (5) longitudinal view for aortic arch and ductus; (6) longitudinal view for systemic veins; and (7) upper axial mediastinal, three-vessel view combined with tracheal location for aortic arch abnormalities.…”
Section: Accepted 21-8-02 Ultrasound In Obstetrics and Gynecologymentioning
confidence: 99%
“…Various types of congenital aortic arch abnormalities have been described; however, most have been reported in the pediatric or radiological literature using magnetic resonance imaging (MRI) and spiral computed tomography (CT) [3][4][5] . Although current prenatal ultrasound technology facilitates identification of many congenital heart defects from early stages of gestation 6 , no information is available regarding aortic arch anomalies during fetal life. Because evaluation of aortic arch abnormalities requires clear definition of the fetal tracheal position in relation to the ductus arteriosus and the aortic arch, we utilized a novel sonographic approach to diagnose these abnormalities which, to the best of our knowledge, has never been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…A análise da influência da idade gestacional sobre o rastreamento das cardiopatias mostra que a taxa de detecção destas doenças, quando obtidas entre a 16ª e a 28ª semana, é 17% maior do que quando as análises são realizadas no primeiro trimestre, devido à existência de anomalias evolutivas 17 . No presente estudo, o resultado que obtivemos com idade gestacional média de 27 semanas pode ter sido determinado pela elevada taxa de sensibilidade do rastreamento e do ecocardiograma fetal em relação ao diagnóstico pós-natal.…”
Section: Discussionunclassified
“…Yagel et al 2 found that 64% of congenital heart defects are detectable during the first transvaginal scan at 13-16 weeks of gestation, and Moyano et al 3 demonstrated that heart malformations can be diagnosed reliably in the first trimester, at the time of nuchal translucency (NT) measurement.…”
Section: Non-invasive Prenatal Testing -It's All a Matter Of Timingmentioning
confidence: 99%